The influence of corporate status symbols in (today's) leadership perception - Rui A. André (Journal of Applied Leadership and Management, 2021)
Research questions: Are status symbols a barrier to intrinsic equality within the organisation? Methods: Quantitative research approach using an anonymous online survey developed and adapted to the research topic, which was published and accessible to economically active individuals with work experience. Results: This research highlights the potential negative impact of status symbols on an employee's intrinsic equality and consequently employee motivation. The research provides value for organisations as it shows that they need to analyse how the perceived equality in their organisational environment is impacted by status symbols.
Keywords: 650